Collaborative governance in the CALFED program: Adaptive policy making for California water - Judith E. Innes; Sarah Connick; Laura Kaplan; David E. Booher (University of California, Institute of Urban and Regional Development (IURD), 2006)
A new, collaborative model of governance has emerged in the CALFED program, which manages much of California 's vast water system. This model emerged out of many years of dialogue among the state's major stakeholders and public agency leaders frustrated by the inability of traditional governance by the three branches-executive, legislative and judicial-to establish significant policy to address the competing needs of the environment and urban and agricultural water users. This paper reports on our research into the history, logic, and workings of this evolving program from its inception as an informal memorandum among agencies in 1994 to its 2004 incarnation with a formal, legislatively established oversight authority. CALFED has unlocked many of the paralyzing stalemates that afflicted California water management in the past; it has built social and political capital among previously warring parties; it has built shared understandings and heuristics among disparate interests and agencies; and it has improved the quality and acceptability of scientific information on which decisions are based. It has allowed just-in-time decision making which is adaptive to rapidly changing natural conditions and needs. The contrast from the traditional governance model to the 'CALFED way' involves eight dimensions. Collaborative processes have replaced gridlock and litigation; a comprehensive framework with linkages and balance among activities replaced project-by-project decisions; multipurpose interagency projects increasingly became the norm rather than single agency projects; local and regional solutions were used instead of just centralized decision making; public involvement was greatly increased, with stakeholders playing leadership roles; independent science reviews modified agency- and client-based science; accountability and transparency of decision making greatly increased; and flexible, adaptive management and joint learning replaced mechanistic decision making based on assumptions and mandates. Whether and how this emergent model of governance can be sustained remains to be seen. Obstacles include the expectations and understandings of many who assess it in terms of a machine model of the world and want to remake it into the traditional model. The strength of collaborative governance is its ability to respond to changing conditions and new information and to create new and unanticipated strategies. The emergence of CALFED converges with the growing recognition in public administration and business that organizations faced by uncertainty, complexity, rapid change and fragmentation must create capacity for adaptation and innovation.
Keywords: 330